POTENSI DAN PERMASALAHAN PENGEMBANGAN TEMULAWAK DI KABUPATEN PURWOREJO - Alfina Handayani; Eny Hary Widowati; Sarjana Sarjana (JURNAL LITBANG PROVINSI JAWA TENGAH, 2010)
This research was aimed to identify potencial and problem of Temu Lawak (Curcuma xathorrhiza Roxb.) cultivation in Purworejo, espesially in term of technology aplication and marketing. Research was conducted during three months from March to May 2009. Research Sample amount to 40 respondents used random sampling method. Data were analysed descriptively, while information of technology application was analysed using scoring approach. The result indicated in term of potencials: 1) Temulawak farming has been embedded in the life of farmer community and passed through the yaounger generation of farmer, since it usually integrated with coconut sugar industry, 2) in general communications behavior of farmers supported the temulawak cultivation, in term of problems: 1) Temulawak farming only contributed 1,12% to overall household income, so that farmer farmer refrained themselves for for taking the risk of intensive cultivation, 2) support and guidance from the relevant government institution have been minimal, 3) the average score of technology aplication in temulawak cultivation was 47,32 % which can be considered as semi-intensive category because, since it was not fully in accordance with the Standart Operating Prosedure (SOP), i.e. seed preparation, planting preparation, planting, fertilization and maintenance. While the cultivation was intensive, pest control was still in a traditional mode, 4) the average score for post harvest technology application was abaut 51,90 %, which can be regarded as technical semi-standart category, 5) Price incentive was very low for farmer and the profit was not evenly distributd, with whosaler reated the moat (72, 29 %) , while farmer gained only 16,79%.